Bifurcation of nonlinear impulsive boundary value problems (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The theory of impulsive differential equations is a very active area of research see for instance  and . Differential equations involving impulsive effects are found in many applications such as mathematical biology, population dynamics, optimal control and so on see  and . There have been many works on the previous mentioned topics and among of them are interested by the study of the existence of solutions for second order impulsive boundary value problems . However, research into bifurcation theory of impulsive differential equations has been modest see  and . Some papers  and  introduced Rabinowitz global bifurcation theorems  to describe the global structure of solutions of second order impulsive boundary value problems